Paparan Particulate Matter 2.5 (PM2.5) Dan Iklim Mikro Sebagai Faktor Risiko Pada Pneumonia Balita Di Daerah Perkotaan - Wahyu Setiaji (PT. Hasba Edukasi Mandiri, 2025)
Pneumonia remains one of the leading cause of death among under-fives in urban areas in Indonesia. PM2.5 fine dust particles as a component of air pollution play a role in increasing the risk of pneumonia through airway damage and decreased immunity. Microclimatic conditions such as temperature, humidity, and rainfall also exacerbate the impact of PM2.5. Factors such as exclusive breastfeeding, nutritional status, vitamin A supplementation, measles immunization coverage, home ventilation, and the surrounding environment are crucial in determining the susceptibility of under-fives to pneumonia. This study used a literature study method with a theme analysis approach and synthesized relevant primary sources published between 2017 and 2025. The results showed a positive correlation between PM2.5 concentrations and the incidence of under-five pneumonia in several urban areas in Indonesia. The complex interactions between PM2.5 exposure, microclimatic conditions, and social, economic, and environmental factors suggest the need for more comprehensive public health interventions. PM2.5 exposure control needs to be accompanied by efforts to improve nutritional status, promote exclusive breastfeeding, immunization, and improve the quality of the home environment as a more comprehensive preventive measure. To support more effective policy development, further research with spatial data and socio-economic aspects is needed to design effective and sustainable urban public health policies.